Nurses Performance in Pain Management for Burn Patient at Baghdad City’s General Hospitals - Al-Umair, kassim; Al-Gersha, Khalida (Iraqi National Journal of Nursing Specialties, 2005)
Abstract A descriptive study was carried out on nurses who were working at burn. Units in Baghdad city hospitals, Al-Kindy , Al-Yarmook, Al-Qadisiya, Al-karkh, and Al-Karama hospital, in the period from 20th july 2003 to 20th November 2003. The study aimed to identify the nurses performance about pain management for burned patients at burn units and find out the relationship between the demographic characteristics and performance . A purposive (non-probability) sample of (40) nurses, (24) male nurses and (16) female. The data were collected through the use of observational checklist, which comprised (38) items distributed on four parts. The validity and reliability of the instrument were determined through a pilot study and by exposing the data to a panel of experts in the field. The data were analyzed through the application of descriptive statistical analysis that includes frequency count, percentages and means, also used inferential statistical analysis that includes the means of scores, chi-square test. The results of the study showed that there was deficiency in nursing management presented by the nurses at burn units. There was significant difference between the performance and level of education. The results of the study showed that the nurses at burn units needs more training for pain management. The study concluded that those nurses should have institute level or more. The study recommended that it is better to develop and improve the nursing staff by continuous educational and training program cessions.